Flow photochemistry: Old light through new windows - Knowles, Jonathan P.; Elliott, Luke D.; Booker-Milburn, Kevin I. (Beilstein Journal of Organic Chemistry, 2012)
Synthetic photochemistry carried out in classic batch reactors has, for over half a century, proved to be a powerful but under-utilised technique in general organic synthesis. Recent developments in flow photochemistry have the potential to allow this technique to be applied in a more mainstream setting. This review highlights the use of flow reactors in organic photochemistry, allowing a comparison of the various reactor types to be made.
Keywords: cycloaddition; flow chemistry; photocatalysis; photochemistry; photooxygenation